Spilling the Beans on Understanding English Idioms Using Multimodality: An Idiom Acquisition Technique for Iranian Language Learners - KHOSHNEVISAN, BABAK (International Journal of Language, Translation and Intercultural Communication, 2019)
Idioms are ubiquitous in English language. Despite their ubiquity, learning idioms is a thorny issue for second language learners. Multiple researchers have scrutinized different aspects of idiom learning by second language learners: important factors in processing idioms in L2 (Cieślicka, 2015); the incorporation of technology in idiom learning (Khoshnevisan, 2018b); idiom assessment (Khoshnevisan, 2018a). A number of studies have been conducted concerning the application of the Idiom Diffusion Model—an L2 idiom processing model—to develop the idiomatic competence of learners, however, the pertinent literature is sparse: Greek, German, and French (Liontas, 1997); Greek (Katsarou, 2013); Korean (Türker, 2016). It turns out that the application of the model to Persian language learners is missing. To address the gap, the author conducted a qualitative study to explore the perceptions of Iranian language learners about using a website to learn idioms. The researcher employed an online questionnaire to delve into the learners’ perceptions. The findings imply that the majority of the participants used video and picture modules to arrive at the figurative meaning of the idiomatic phrases. However, in terms of semi and post-lexical idioms, most learners benefited from translations to decode the meanings. The findings corroborate the theory that translation facilitates learning idioms.